1996
DOI: 10.1002/(sici)1096-8628(19960614)63:3<438::aid-ajmg5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile myoclonic epilepsy in chromosome 6p12-p11: Locus heterogeneity and recombinations

Abstract: We recently analyzed under homogeneity a large pedigree from Belize with classic juvenile myoclonic epilepsy (JME). After a genome wide search with 146 microsatellites, we obtained significant linkage between chromosome 6p markers, D6S257 and D6S272, and both convulsive and EEG traits of JME. Recombinations in two affected members defined a 40 cM JME region flanked by D6S313 and D6S258. In the present communication, we explored if the same chromosome 6p11 microsatellites also have a role in JME mixed with pykn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Clarke et al [27] found a migraine prevalence of 15% in children with the homogenous epilepsy subtype rolandic epilepsy in contrast to 7% in non-epilepsy probands. Since JME has a strong genetic background (positive family history of seizures in at least 40% [10]), headache and especially MA in JME, but maybe not in the general population, might also have such a strong genetic background. We suggest that our findings support using the relationship of JME and MA to further study the genetics of both disease entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarke et al [27] found a migraine prevalence of 15% in children with the homogenous epilepsy subtype rolandic epilepsy in contrast to 7% in non-epilepsy probands. Since JME has a strong genetic background (positive family history of seizures in at least 40% [10]), headache and especially MA in JME, but maybe not in the general population, might also have such a strong genetic background. We suggest that our findings support using the relationship of JME and MA to further study the genetics of both disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…The main seizure types are myoclonic jerks, generalized tonic-clonic seizures and, less frequently, absences [9]. The syndrome has a strong genetic background with at least 40% of patients presenting a positive family history [10]. Intensive genetic studies could identify genes associated with JME coding for various ion channels, but also acetylcholine receptors, lysosomal membranes, and for the regulation of apoptosis (review in [11]).…”
Section: Introductionmentioning
confidence: 99%
“…By fluorescence in situ hybridization analysis, we mapped the KCNQ5 gene to chromosome 6q14. There are two known loci on chromosome 6 linked to epileptic diseases, a cloned gene at 6q24 (EPM2A), which is defective in progressive myoclonic epilepsy type 2 (40,41), and an unknown gene mapped to 6p12-p11, which is responsible for juvenile myoclonic epilepsy (JME) (42). Although our mapping results probably exclude involvement of KCNQ5 in JME, the identification of KCNQ5 makes it now possible to investigate possible associations with other forms of epilepsy or inherited neurological diseases.…”
Section: Fig 2 Tissue Distribution Of Human Potassium Channel Kcnq5mentioning
confidence: 99%
“…Since both JME and migraine are highly linked to genetic and hereditary basis, in our study positive family history of migraine was found to a higher incidence in JME cases with migraine 60 % compared to only 25% positive family history of migraine JME cases with migraine which supports a strong genetic background (25).…”
Section: Ito Et Al(22)mentioning
confidence: 99%